Historiography and ldentity IV: The Writing of History Across Medieval Eurasia - Pohl, Walter; Mahoney, Daniel (2021)
The volume extends the mainly European focus of the series 'Historiography and ldentity' to probe into a more global perspective, exploring the historiographical cultures of a number of Eurasian macro-regions: China, Japan, Iran, South Arabia, Syria, Byzantium, Lotharingia, and Spain. The broader, Eurasian perspective can contribute to a deeper understanding of the very different ways in which works of historiography could communicate, promote, and negotiate 'visions of community' and concepts of belonging.